Transposition of the Concept of Imāmah al-Mawardi into the Islamic Education Leadership System - Miftahussurur, Wildan; Hakim, Lukman; Sholihan, Amilah (UII Darullughah Waddawah Pasuruan, 2025)
Leadership in Islamic education is not only administrative, but also spiritual and moral. The concept of imāmah according to Imam al-Māwardī offers ideal leadership principles that are relevant to address the challenges of contemporary Islamic education. However, until now there have not been many educational leadership models that systematically adapt these principles. This study explores the concept of imāmah as articulated by Imām al-Māwardī and its relevance to leadership in Islamic education. In the educational context, leadership goes beyond administrative management; it encompasses spiritual and moral guidance grounded in Islamic values. Through his seminal work al-Aḥkām al-Sulṭāniyyah, al-Māwardī outlines the essential qualities of an ideal imām—including justice (ʿadālah), knowledge (ʿilm), trustworthiness (amānah), wisdom (ḥikmah), and a commitment to consultative governance (shūrā). Employing a qualitative approach with descriptive analysis, this research investigates the values embedded in al-Māwardī’s theory of leadership and applies them to the framework of Islamic educational leadership. The findings suggest that integrating the principles of imāmah can foster a leadership model that is ethically sound, spiritually conscious, and adaptable to contemporary educational challenges. By embracing the values of justice, knowledge, and participatory leadership, Islamic educational leaders can cultivate a nurturing ecosystem that promotes character development and spiritual growth among students. This study aims to contribute both theoretically and practically to the advancement of a holistic and contextually relevant model of Islamic educational leadership.